KESIMETRISAN DALAM SISTEM DEMONSTRATIVA BAHASA MANDAILING - Hasibuan, Namsyah Hot (LITERA, 2015)
Abstract This study aims to describe the demonstrative system in the Mandailing language. The data were collected from native speakers in their daily communication. They were analyzed by classifying demonstrative expressions based on Levinson's theory and their uses were described in accordance with field observations and informants' explanation. The results of the study are as follows. First, there are three types of relative distances for object reference. The object reference in the three types of relative distances uses a particular demonstrative expression. Second, a demonstrative expression for each relative distance has the same base. This shows that there is a symmetric relationship among demonstrative expressions. The object relatively close to the speaker is referred to by a demonstrative expression using the element on. The object relatively distant from the speaker but it is close to the addressee is referred to by a demonstrative expression using the element i. The object relatively distant from the speaker and the addressee is referred to by a demonstrative expression using the element odu.